Pediatric neglected distal femoral fracture with growth arrest - Muhammad, Hilmi; Filza, Muhammad Riyad; Siwendro, Afrisya Bimo; Ismiarto, Yoyos Dias (Elsevier Ltd, 2022)
Introduction and importance: Distal femoral growth plate fracture is one of the most common growth plate fractures in the pediatric age, and associated with growth disturbance risk. Consequences that may arise are hindered growth, irreversible decrease in range of motion, instability, angular deformity and neurovascular issues. Fractures of the lateral condyle show a higher risk of developing sequelae compared to the medial side. Case presentation: Corrective osteotomy of the distal femur was performed in patient with history of femoral fracture which undergone an ORIF procedure for the shaft at the previous hospital, while the lateral condyle fracture was treated conservatively. We did close wedge osteotomy medially and transferred the bone fragment to the lateral side as an open wedge to lengthen the lateral cortex. The leg-length discrepancy was reduced from 5 to 2 cm even though subsequent deformities may possibly occur. Clinical discussion: The management approach for fracture of distal femoral physis can be done conservatively or surgically. Unfavorable outcomes from the conservative approach gave more reasons to opt for a surgical approach. The growth plate location should be considered when deciding which level of osteotomy is best and the fixation points in younger patients. When physeal bars are formed due to the fracture stress on the growth plate, the treatment is based on the patient's age and the bar's size. Conclusion: Fractures of the distal femur involving a growth plate in children should not be considered a trivial case, and a comprehensive treatment plan should be coordinated. © 2022 The Authors